Economic and environmental analyses of incorporating guar into the American southwest. (June 2021) - Summers, Hailey M.; Sproul, Evan; Seavert, Clark; Angadi, Sangu; Robbs, Joram; Khanal, Sita; Gutierrez, Paul; Teegerstrom, Trent; Zuniga Vazquez, Daniel A.; Fan, Neng; Quinn, Jason C.
Abstract: CONTEXT: Persistent drought is affecting the livelihood of American farmers in arid climates. Adopting drought-tolerant crops, such as guar ( Cyamopsis tetragonoloba L.), is one potential solution for improving economic revenue and reducing the effect of drought on farms. Guar produces guar gum, which is a thickening and stabilizing agent in fluids used most recently in the hydraulic fracking of shale oil and gas recovery. OBJECTIVE: This study was performed to investigate the economic and environmental feasibility of cultivating guar in the American Southwest and transporting it to a domestic processing facility for the primary product of guar gum. METHODS: An integrated techno-economic (TEA) and life cycle analysis (LCA) was performed on the cradle-to-gate process of producing guar gum for domestic supply in the United States. TEA was performed to investigate the economic performance on the farm and downstream for the guar gum production facility. Similarly, the LCA investigated the environmental impact to the farm and the primary product of guar gum. RESULTS AND DISCUSSION: Baseline results indicate a minimum selling price of $1.44 per kg-guar gum, driven largely by irrigation, herbicides and associated equipment use. A best case economic scenario where irrigation and fertilizers were removed, low-cost herbicides were used and less intensive land management practices were adopted, highlights the feasibility of guar gum being produced for as low as $0.45 per kg-guar gum, which is lower than the five-year average U.S. import price of $0.99 per kg-guar gum. Environmental impacts of guar gum are largely attributed to irrigation and agricultural equipment use. The indicator, global warming potential, resulted in farm-level emissions of 1160 per hectare of guar grown. The combined farm, transportation and downstream processing production processes results in 2.67 kg CO2 eq per kg-guar gum, or 806 kg CO2 eq per hectare, which is lower than the farm emissions due to a co-product credit for animal feed. SIGNIFICANCE: The economic results indicate that guar gum can be produced for less than average U.S. import prices. The environmental impact results indicate that growing guar would lead to lower emissions than existing crops when cultivated in the American Southwest. Graphical abstract: Unlabelled Image Highlights: Economic and environmental analyses of producing guar gum in the American Southwest. Baseline economics result in a minimum selling price of $1.44 per kilogram guar gum. Baseline global warming potential results are 2.67 kg CO2 eq per kilogram guar gum. Best case scenario results show guar can be an economically and environmentally advantageous crop.